Editorial. (September 2014) - Alderman, Lyn; Clinton, Janet; Harvey, Graeme
This is an exciting time for the Evaluation Journal of Australasia (EJA) as it embarks on a new phase. As we launch a new design and move to an online format, it is our hope that EJA is enhanced as a resource for evaluators and one that supports the growth of evaluation. With a new approach and a contemporary look and feel, we believe that the journal will add value to the profession and the discipline that is evaluation. By promoting research on evaluation and celebrating practice, evaluation in Australasia may flourish.